Quality of life of deaf and hard of hearing students in Ibadan metropolis, Nigeria (2018)
Quality of Life encompasses an individual's well-being and health, social participation and satisfaction with functional daily living. Disabilities such as deafness can impact on the quality of life with spatial variance to the environment. Deafness causes communicative problems with significant consequences in cognitive, social, and emotional well-being of affected individuals. However, information relating to the quality of life of deaf and hard of hearing individuals, especially students in developing countries like Nigeria, which could be used to design special health-related interventions is sparse. This study examined the quality of life of deaf and hard of hearing students in Ibadan metropolis, Nigeria. One hundred and ten deaf and hard of hearing students participated in this cross-sectional study. Participants were drawn from all four secondary schools for the Deaf in Ibadan metropolis. The 26 item Brief version of the WHO Quality of Life questionnaire was used for data collection. The data was analyzed using descriptive and inferential statistics at statistical significance of p<0.05. Majority (57.8%) of the deaf and hard of hearing students had poor quality of life. Attending the special school for the Deaf, upper socio-economic status and age (≥17years) are significantly associated with better quality of life. However, gender and age at onset of hearing loss had no significant influence on the quality of life. The Deaf community available in the special school appeared to protect against stigma and discrimination, while also promoting social interactions between deaf and hard of hearing individuals